Relationship between Social Support and COVID-Related Common Mental Disorders Incidence in Pregnant Women in Banyumas, Central Java - Fadel Rahman; Yudhi Wibowo; Purwa Riana (Indonesian Journal of Medicine, 2023)
Background:  Social restriction and distancing were enforced, to contain the viral transmission of Coronavirus Disease-19 (COVID-19). Therefore, normal social activities are stagnant and give rise to common mental disorders (CMDs) in pregnant women, especially in the first trimester of pregnancy. The purpose of this study was to analyze the relationship of social support with COVID-related common mental disorders (CMDs) in pregnant women in Banyumas Regional General Hospital.Subjects and Method:  A observational analytic study using a Cross-sectional study approach targeting pregnant women in the Banyumas Regency Central Java, from May to December 2022. The independent variable is social support. The dependent variable is common mental disorders (CMDs). The sampling technique used snowball sampling of approximately 1543 respondents. This study employed the WHO-SSQ-6 and WHO-SRQ-20 questionnaires. The data analysis technique made use of the Chi-Square test.Results:  Pregnant women who have low social support have a risk of Common Mental Disorders (CMDs) and are statistically significant (PR= 1.74; 95% CI = 1.83 to 1.87; p<0.001).Conclusion:  Social support has a significant correlation with COVID-related CMDs.Keywords:  COVID-19, COVID-related CMDs, Pregnant women, first trimesterCorrespondence:  Yudhi Wibowo, Department of Public Health and Community Medicine, Faculty of Medicine, Jenderal Soedirman University. Jl. Dr. Gumbreg No.1, South of Purwokerto, Banyumas Regency, Central Java. Email: dryudhiwibowo2005@gmail.com. Mobile: +62 811-2621-904.Indonesian Journal of Medicine (2022), 08(02): 142-149https://doi.org/10.26911/theijmed.2023.08.02.03